Force majeure in commercial contracts - Symons, Ben; Daly, Joseph (London [England] : Bloomsbury Professional, 2022)
"Principally concerned with the laws of England and Wales, Ireland and Australia with references to other common law jurisdictions, EU and international law where relevant, Force Majeure and Frustration in Commercial Contracts looks at both doctrines of force majeure and frustration and their application to commercial contracts. It sets out the statutory principles that apply. Whilst looking at these principles in a broad sense, it is also the first major work to relate them to and address the issues brought about by the COVID19 pandemic. Written by leading experts and practical in approach, it is essential reading for commercial practitioners and contract lawyers to ensure that they avoid the consequences of a breach of contract caused by events outside their control which delays, hinder or prevent performance."--
Chapter 1: Introduction to Force Majeure -- Chapter 2: General Principles of Contractual Interpretation -- Chapter 3: What constitutes a "force majeure" event? -- Chapter 4: Prevent, hinder and/or delay -- Chapter 5: Beyond reasonable control -- Chapter 6: Causation -- Chapter 7: Notice -- Chapter 8: Material adverse change ((3z(BMAC(3y(B) clauses -- Chapter 9: Force majeure in international case law -- Chapter 10: Frustrations
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily.
Mode of access: World Wide Web.
Keywords: Contracts; Vis major (Civil law); Commercial law; Electronic books